Podstawowe tendencje w rozwoju polskiej przestrzeni - źródła i kierunki - Miszczak, Katarzyna (Basic Trends of Polish Space Development - Sources and Directions, 2005)
The main aim of this article is showing basic tendencies of Polish space development which has just now occured in situation of definition and forming of development's directions, coming inter alia off process of integration with the European Union. The basic problem of Polish spatial structure, threatening social and economic cohesion, are disparities between eastern and western parts of Poland, depopulation of considerable areas left without bright and realistic vision of development, and chaotic development of metropolitan areas.However, observation of modern mechanisms and processes getting in space allows to ascertain, that big cities or great metropolitan areas in range of stimulation of development and conducts of international cooperation have already played a role not only on regional scale but even supraregional. They become strong actors decisive about the rate and directions of regions and country's development.In the article there was paid special attention for conception of policy of country spatial development and model of balanced development.As a reason of the elaboration's limited volume, presented matters, opinions and conclusions were depicted in synthetic form.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 202-211